Breaking Barriers: How Telemedicine is Reshaping Access and Quality in Healthcare - Shweta Tomar (Emerging Trends in Personalized Medicines, 2024)
Thanks to advancements in telecommunications technology, telemedicine has become a disruptive force in the delivery of healthcare, bridging geographical and accessibility gaps. This article offers a thorough examination of the advantages, difficulties, and potential applications of telemedicine in healthcare. Telemedicine has a number of benefits, one of which is that it makes healthcare more accessible, especially for underprivileged groups living in rural or isolated places. Telemedicine makes it possible for patients to consult with medical specialists remotely, removing the need for travel and other geographical restrictions. Also, telemedicine improves continuity of care for patients with illnesses like diabetes and hypertension by facilitating regular follow-ups and chronic disease monitoring Telemedicine has various drawbacks and obstacles in spite of its advantages. Healthcare disparities are made worse by the digital divide, which prevents people with limited technology or internet connectivity from accessing telemedicine services. Moreover, it is concerning that there could be misdiagnoses or misinterpretations during virtual consultations, especially in complicated instances that call for physical exams or diagnostic tests. Telemedicine has a great deal of potential for future improvements and breakthroughs. The capabilities of telemedicine systems are expected to be expanded by emerging technologies like wearables, artificial intelligence, and remote monitoring tools. This will allow for more comprehensive and customised patient care. Furthermore, by dismantling organisational silos and fostering knowledge exchange and interdisciplinary collaboration among healthcare professionals, telemedicine might enhance patient outcomes and care coordination. Furthermore, telemedicine's potential for preserving continuity of care and lowering exposure risks is highlighted by its role in disaster response and public health situations, as seen during the COVID-19 pandemic.
Keywords: Telemedicine; digital divide; healthcare accessibility; healthcare innovation; remote monitoring